2020
DOI: 10.1128/aem.00527-20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide GH12 Prevents Dental Caries by Regulating Dental Plaque Microbiota

Abstract: ABSTRACT Due to the complex microecology and microenvironment of dental plaque, novel caries prevention strategies require modulating the microbial communities ecologically and reducing the cariogenic properties effectively. Antimicrobial peptide GH12 reduced the lactic acid production and exopolysaccharide (EPS) synthesis of a Streptococcus mutans biofilm and a three-species biofilm in vitro Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…[ 149 ] An in vivo study reported that GH12, a cationic amphipathic α ‐helical AMP, reduced the production of exopolysaccharides by S. mutans biofilms and decreased the acidity of the microenvironment. [ 153 ] Peptide polyphemusin I is another natural AMP isolated from horseshoe crabs that contain 17 to 18 amino acids. [ 154 ] In vitro and in vivo results confirmed the antimicrobial properties of the peptide polyphemusin I.…”
Section: Gene and Protein Deliverymentioning
confidence: 99%
“…[ 149 ] An in vivo study reported that GH12, a cationic amphipathic α ‐helical AMP, reduced the production of exopolysaccharides by S. mutans biofilms and decreased the acidity of the microenvironment. [ 153 ] Peptide polyphemusin I is another natural AMP isolated from horseshoe crabs that contain 17 to 18 amino acids. [ 154 ] In vitro and in vivo results confirmed the antimicrobial properties of the peptide polyphemusin I.…”
Section: Gene and Protein Deliverymentioning
confidence: 99%
“…This microecology not only provides a great haven for the reproduction of caries pathogens and the fermentation of an acidic environment ( Filoche et al, 2010 ) but also resists attack from foreign substances, including antibiotics and antibacterial agents ( Pizzolato-Cezar et al, 2019 ). Many agents have an antibacterial effect on cariogenic pathogens in suspension ( Jiang et al, 2020 ; Zhang et al, 2021 ), but it is extremely difficult for these agents to penetrate into biofilm and attack the pathogens in the biofilm. This is a major challenge for the clinical applications of these agents for dental caries management.…”
Section: Introductionmentioning
confidence: 99%
“…Together, our results indicate that OMVs derived from certain bacteria may be a viable adjunct therapy to enhance the effectiveness of antibiotics against bacterial biofilms. They could also be used in conjunction with other new antibiofilm therapeutics, such as recently described antimicrobial peptides D-CONGA and GH-12 that display antibiofilm activities [51,52].…”
Section: Discussionmentioning
confidence: 99%